Moral damages, criteria that determine its compensation (UNIHumanitas, 2021)
This article has been a review of legislation, doctrine and jurisprudence on contractual and non-contractual liability for pain and suffering damages, whose objective was the analysis of the criteria followed for the determination of its existence and scope. The methodology used was a descriptive literature review. The main sources of information used were the most relevant doctrine on the subject, the regulations of the Paraguayan Civil Code and some rulings of the Civil Chamber of the Supreme Court of Justice of Paraguay from 2016 to 202, on contractual and tort liability for moral damages. As main conclusions the following were obtained: for the reparation of moral damages, it must be proven in all proceedings that the agent caused the victim an affliction, an impairment of his feelings or the disruption of his spiritual balance, and that this must be linked to the basic assumptions for all damage reparation, which are the wrongful act or breach of obligation, moral damages, attribution factor, causal link between the wrongful act or breach and moral damages;  that the function of the compensation for moral damages is compensatory or compensatory in nature, and cannot be considered as a sanction; and that its quantification is left to the prudent judicial criterion, the judge must take into consideration the circumstances of each particular case.
Keywords: civil liability; estimate of the damage; non-material damage; quantification